Virtualization of the seminar class under conditions of a spatial removal - Vasilaki, Viktor; Bolz, Markus; Ryzhov, Alexey; Рижов, Олексій Анатолійович (Запорізький державний медичний університет, 2020)
The use of conference systems supported by different providers is not new. The Microsoft Teams system, which is discussed in this article, in particular Teams Rooms, is not the company's first development (Microsoft Lync 2013 and Skype for Business were already a meeting room system).